Dye affinity chromatography of ricin subunits. Issue 12 (December 1986) - Sperti, Simonetta; Montanaro, Lucio; Rambelli, Fioretta
Abstract : A rapid and simple method for the isolation of the two chains of ricin is described. The method involves two chromatographic runs, the first on blue-Sepharose and the second on blue dextran-Sepharose. It is moreover shown that the A chain of ricin, but not the B chain, binds to poly(U)-Sepharose.